Ovarian hyperstimulation closely associated with resumption of follicular growth after chemotherapy during tamoxifen treatment in premenopausal women with breast cancer: a multicenter retrospective cohort study - Rena Yamazaki; Masafumi Inokuchi; Satoko Ishikawa; Takuya Ayabe; Hiromitsu Jinno; Takashi Iizuka; Masanori Ono; Subaru Myojo; Soko Uchida; Toshiya Matsuzaki; Akira Tangoku; Masato Kita; et al. (BMC Cancer, 2020)
Abstract Background We previously reported that tamoxifen (TAM)-induced ovarian hyperstimulation (OHS) is associated with high serum concentrations of estradiol in premenopausal women with breast cancer. To investigate risk factors for TAM-induced OHS, we performed a retrospective multicenter study. Methods Premenopausal patients who received surgical therapy for endocrine-dependent breast cancer (n = 235) were recruited in this study and classified into 4 groups: group A, treated with TAM alone; group B, TAM treatment after 2-year-combined therapy with a gonadotropin-releasing hormone (Gn-RH) agonist; group C, TAM treatment after chemotherapy; group D, 5-year-combined therapy with TAM and a Gn-RH agonist. A serum estradiol value of more than 300 pg/mL or mean follicular diameter of more than 30 mm was defined as OHS. Results The incidence of OHS in group A (n = 13/26, 50.0%) was significantly higher than those in group B (n = 17/63, 27.0%), group C (n = 20/110, 18.2%), and group D (n = 0/36, 0%). The incidence of OHS was significantly correlated with aging, and the median serum concentration of estradiol in the presence of OHS was 823.0 pg/mL. The incidence of OHS (less than 47 years old) was 62.5% in group A, 48.6% in group B, and 28.2% in group C, respectively. Notably, the incidence rate of OHS following amenorrhea in group C (n = 13/20, 65.0%) was significantly higher than that in group B (n = 1/17, 5.9%). Conclusions These findings indicate that the onset of OHS following amenorrhea was common in the post-chemotherapeutic group, while its ratio was low in the group after Gn-RH analog treatment, suggesting that combined treatment-based management involving TAM therapy is necessary for premenopausal patients with breast cancer.